Psychometric sifting to efficiently select the right service employees. Issue 5 (2014) - John E.G. Bateson; Jochen Wirtz; Eugene Burke; Carly Vaughan
<x xml:space="preserve"> Abstract </x> Purpose – Service employees in subordinate service roles are crucial for operational efficiency and service quality. However, the stressful nature of these roles, inappropriate hire selection, and the proliferation of job boards have created massive recruitment problems for HR departments. The purpose of this paper is to highlights the growing costs of recruiting the right candidates for service roles while offering an alternative approach to recruitment that is more efficient and effective than the traditional approach. Design/methodology/approach – The study offers empirical evidence of five instances in which the use of psychometric sifting procedures reduced recruitment costs, while improving the quality of the resultant hires. Findings – By standing the traditional recruitment process "on its head" and using psychometric tests at the start of the selection process, the recruitment process can be significantly improved. Such tests efficiently weed out unsuitable candidates before they even enter the recruitment process, leaving a smaller, better‐qualified pool for possible recruitment. Practical implications – Firms can safely use the psychometric sifts to select applicants according to their operational efficiency, customer orientation, and overall performance. This paper illustrates the use of both traditional questionnaire measures and situational judgment tests to remove unsuitable applicants at the start of the selection process. A real‐life case study suggests that such an approach increases the hiring success rate from 6:1 to 2:1. In the opening of a new supermarket by a UK group, this process saved 73, 000 hours of managers' time, representing 1.8 million savings in opening costs. Originality/value – The paper offers a viable cost‐saving alternative to a growing problem for HR departments in service firms and provides directions for further research. <ack> <x xml:space="preserve"> Acknowledgements </x> This paper builds on a condensed version of b2Bateson et al. (2013). </ack>